HIPPOS - Jaycox, Jaclyn, 1983-; Chester, Gena; Huff, Abby (North Mankato, Minnesota : Pebble, an imprint of Capstone, 2022)
"Hippos are one of the largest land mammals in the world! These big vegetarians prefer to spend their time in the water. Readers will enjoy learning more about hippos with . . . facts and . . . photos"--Provided by publisher
Includes index
"Pebble explore"--Back cover.
Bibliography : page 31
Keywords: Hippopotamus -- Juvenile literature